PENINGKATAN KEMAMPUAN MEMBUAT VIDEO CUT OUT ANIMATION BAGI SANTRI PONDOK PESANTREN ROUDLOTUL MUDARITSIN KUNINGAN - Yulyanto, Yulyanto; Supriyadi, Sugeng; Krisdiawan, Rio Andriyat; Lesmana, Iwan; Rasul, Muh Abi (Empowerment, 2020)
The Community Disablement activity was carried out against the background of lack of knowledge about computer science, especially in the field of video animation among boarding school students. With this activity, it is expected to be able to improve their abilities in the field of animation and video editing, especially cut-out animation so that the students can develop their artistic spirit. The cut out animation video created is expected to be a means of conveying positive messages to the public. As we know lately a lot of irresponsible information that contains violence, hatred and heresy, this activity is expected to stimulate students to make videos or positive information content, to counteract the large amount of irresponsible information, with the ability making this animated video also expected students to package their da'wah becomes more interesting. This Community Service was conducted at the Raoudlotul Mudaritsin Islamic Boarding School in Sukamukti Village, Jalaksana District, Kuningan Regency and was attended by 30 students. Where the final result of this devotion is to make a cut-out animated video product created by the students. Thus, the students have the knowledge and experience step by step to make an animated cut-out videoKegiatan Pengabidan Masyarakat ini dilakukan dengan latar belakang minimnya pengetahuan mengenai ilmu komputer khususnya dalam bidang animasi video dikalangan santri pondok pesantren. Dengan adanya kegiatan ini, diharapkan dapat meningkatkan kemampuannya dibidang animasi dan video editing khususnya cut out animation sehingga para santri dapat mengembangkan jiwa seni yang dimilikinya. Video animasi cut out yang dibuat diharapkan dapat menjadi sarana menyampaikan pesan-pesan positif kepada masyarakat. Sebagaimana kita ketahui akhir-akhir ini banyak sekali informasi yang tidak bertanggungjawab yang berisikan kekerasan, kebencian dan ajaran sesat, kegiatan ini diharapkan dapat merangsang para santri untuk membuat video atau konten informasi  yang positif, guna menangkal banyaknya informasi yang tidak bertanggung jawab tersebut, dengan kemampuan membuat video animasi ini diharapkan juga santri dapat mengemas dakwahnya menjadi lebih menarik. Kegiatan Pengabdian ini dilakukan di Aula Pondok Pesantren Raoudlotul Mudaritsin Desa Sukamukti Kecamatan Jalaksana Kabupaten Kuningan dan diikuti oleh 30 santri. Dimana hasil akhir dari kegiatan pengabdian ini adalah membuat produk video animasi cut out hasilkarya para santri. Sehingga, para santri memiliki pengetahuan dan pengalaman langkah demi langkah membuat video animasi cut out